Design and Construction of Inductive Compensation for Extra-High-Voltage Transmission Line Models of Physical Laboratory of Electric Power Systems - Anderson Anrrango Delgado; Anghelo Navarrete Cumbal; Jesús Játiva Ibarra (Engineering Proceedings)
The implementation of inductive compensation in the two-scale models of the extra-high-voltage transmission line, without and with transposition, of the Physical Laboratory of Electric Power Systems (PLEPS) is presented. As they have voltages above the normal operating range, for a situation like that of the real 500 kV Coca Codo Sinclair–El Inga lines in Ecuador, the problem was solved by incorporating parallel inductive reactors located at the ends of the lines. The fixed bus compensation used was carried out by means of three-phase inductors in star connection with neutral-to-ground voltage and built-in iron cores with pitches of 50, 75 and 100% of the design capacity.